“New York and yet not New York”: Reading the Region in Contemporary Brooklyn Fictions - James Peacock (European Journal of American Studies)
The article analyzes the depiction of Brooklyn as an urban region in a number of recent American novels, including Lynne Sharon Schwartz’s Leaving Brooklyn and Kitty Burns Florey’s Solos. It argues that Brooklyn is frequently defined in opposition to Manhattan: the former being viewed as the epitome of American ideals of community-in-diversity, the latter as homogenizing, globalizing and obsessed with newness. In a time when regions and communities are frequently regarded as under threat from, amongst other things, globalization and terrorism, it is interesting to examine whether the ideals of diversity and community associated with Brooklyn are based on nostalgic, mythic notions of land and family or are in fact based on superficial signifiers of diversity and a range of consumer choices. The article goes on to argue that the complex interactions between the regional and the global in these novels can be seen as analogous to processes of reading regional texts themselves.